Strategic intelligence in preventing radicalism and terrorism: A study in Cilacap - Costazolanitova, Briyan; Rofii, Muhammad Syaroni; Priyanto, Sapto (International Journal Labs, 2023)
This research discusses how the Cilacap Polresta's strategic intelligence in dealing with conditions where there is a Nusakambangan Prison where terrorism convicts are detained. there are prisoners of terrorism convicts and families and organizations affiliated with terrorism in the jurisdiction of the Cilacap Polresta. Based on the background, there are 2 main problems that underlie this title namely 1) What is the pattern of the spread of radicalism in Cilacap? 2) What is the Cilacap Police intelligence strategy in preventing radicalism? The theory that underlies the research is the theory of strategic intelligence and national resilience. Strategic intelligence in law enforcement agencies, is carried out as planning without considering and studying the crime problems faced by the agency and without adequate operational input, while national resilience is a dynamic aspect of a nation that includes all aspects of national life to remain victorious in the midst of regularity and change that always exists. The research method design used to analyze this research is descriptive qualitative, the data collection techniques used are interviews and literature studies. Then where the data collected is then analyzed with theories related to strategic intelligence and national resilience. The results of this study are expected to be one source of information about the pattern of the spread of radicalism, as well as understanding the mechanism of intelligence strategy in preventing radicalism in society.